Japanese Schoolteachers' Attitudes and Perceptions Regarding Inclusive Education Implementation: The Interaction Effect of Help-Seeking Preference and Collegial Climate - Maeda, Kaede; Hashimoto, Hirofumi; Sato, Kosuke (Frontiers in Education, 2021)
While the special needs education system in Japan has shifted from a segregated approach to a more inclusive one, the actual implementation of this approach may be less than ideal. The implementation of inclusive education faces several challenges, such as difficulty in meeting individual needs and lack of medical support systems in general school settings. With this in mind, we conducted a web-based survey of Japanese schoolteachers to empirically examine their attitudes and perceptions regarding inclusive education. We also sought to determine the socio-environmental and individual factors that affect the attitudes and perceptions of Japanese elementary and junior high school teachers regarding the implementation of inclusive education. Survey results showed that schoolteachers regard the idea of inclusive education as desirable, but not feasible. However, we found that schoolteachers' perceptions of the feasibility of inclusive education implementation were positively associated with their help-seeking preference if they perceived their climate as being sufficiently collegial. Based on these findings, we discuss the educational environment in which inclusive education could be successfully implemented.